Pembuatan masker aerator untuk atlet difabel sebagai pencegahan hypoxia saat latihan di masa pandemi COVID-19 - Faiz Nur Fauzi; Diasdamara Fakhri Nugroho; Rizqi Husain Alfathan; Wijang Wisnu Raharjo; Bambang Kusharjanta; Ubaidillah (Badan Kerja Sama Teknik Mesin Indonesia, 2022)
During the current COVID-19 pandemic, we are encouraged to always obey health protocols. One of them is to use a mask. The use of masks on athletes, especially athletes with disabilities has a bad impact on the athlete's body itself. Because in the course of training, the athletes will do heavy work that requires adequate oxygen supply. In this case, the mask can reduce the athlete's respiratory effectiveness due to hypoxia. Hypoxia is a condition in which the body lacks oxygen levels. To prevent hypoxia in athletes who must continue to carry out training with the COVID-19 health protocol is to use a mask that can regulate air circulation properly. Therefore, an idea emerged to make an aerator mask that can help the respiratory system and can prevent athletes from getting hypoxia during training during a pandemic, because the aerator mask that we made is equipped with dual fans that can supply oxygen properly. Thus, athletes can exercise without fear of experiencing hypoxia disorders and remain compliant with health protocols.